Draft Annual Plan 1982-83 Union Territory of Lakshadweep - Planning Commission (Planning Commission, 1982)
Coconut is the main stay of the people of Lakshadweep. It is the only crop of Agricultural importance grown in this Union Territory. The entire cultivable area of 2780 are fully covered with coconut plantation. The coconuts are grown purely in rainfed conditions. The Agro-ecological conditions in the islands support the coconut cultivation. The coconut production target for the last year of the Sixth Five Year Plan is 235 lakh units. The soils in all the islands are fairly homogenous in their composition and texture. They are partially coral soils underlined by grades of different sizes and shapes.
Union Territory of Lakshadweep